Severity of local inflammation does not impact development of fibrosis in mouse models of intestinal fibrosis. Issue 1 (December 2018) - Hünerwadel, A.; Fagagnini, S.; Rogler, G.; Lutz, C.; Jaeger, S.; Mamie, C.; Weder, B.; Ruiz, P.; Hausmann, M.
Abstract Intestinal fibrosis is thought to be a consequence of excessive tissue repair, and constitutes a common problem in patients with Crohn's disease (CD). While fibrosis seems to require inflammation as a prerequisite it is unclear whether the severity or persistence of inflammation influences the degree of fibrosis. Our aim was to investigate the role of sustained inflammation in fibrogenesis. For the initiation of fibrosisin vivo the models ofIl10 −/− spontaneous colitis, dextran sodium sulfate (DSS)-induced chronic colitis and heterotopic transplantation were used. InIl10 −/− mice, we determined a positive correlation between expression of pro-inflammatory factors (Il1β, Tnf, Ifnγ, Mcp1 andIl6 ). We also found a positive correlation between the expression of pro-fibrotic factors (Col3a1 Col1a1, Tgfβ andαSma ). In contrast, no significant correlation was determined between the expression of pro-inflammatoryTnf and pro-fibroticαSma, Col1a1, Col3a1, collagen layer thickness and the hydroxyproline (HYP) content. Results from the DSS-induced chronic colitis model confirmed this finding. In the transplantation model for intestinal fibrosis a pronounced increase inMcp1, inos andIl6 inIl10 −/− as compared to WT grafts was observed, indicating more severe inflammation inIl10 −/− grafts. However, the increase of collagen over time was virtually identical in bothIl10 −/− and WT grafts. Severity of inflammation during onset of fibrogenesis did not correlate with collagen deposition. Although inflammation might be a pre-requisite for the initiation of fibrosis our data suggest that it has a minor impact on the progression of fibrosis. Our results suggest that development of fibrosis and inflammation may be disconnected. This may be important for explaining the inefficacy of anti-inflammatory treatments agents in most cases of fibrotic inflammatory bowel diseases (IBD).